2022
DOI: 10.21203/rs.3.rs-2353929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic impact of blood urea nitrogen to albumin ratio on patients with sepsis: A retrospective cohort study

Abstract: Objective To investigate the ability of the ratio of blood urea nitrogen (BUN) to serum albumin ratio (BAR) in patients with sepsis in intensive care units (ICUs) to predict the prognosis of short-and long-term death. Methods Data were derived from the Medical Information Market in the Intensive Care IV (MIMIC-IV v2.0) database, with septic patients defined by SEPSIS-3. 30-day mortality for the primary outcome and 360-day mortality for the secondary outcome. Kaplan-Meier (KM) Survival curves were plotted to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Recently, BAR has been used as a new biomarker to assess the prognosis of various diseases and is an important prognostic factor for death in several diseases, such as pulmonary embolism, 25 sepsis, 9 and lung cancer 26 . Moreover, numerous studies have identified BAR as an independent predictor for mortality risk of AMI 30,39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, BAR has been used as a new biomarker to assess the prognosis of various diseases and is an important prognostic factor for death in several diseases, such as pulmonary embolism, 25 sepsis, 9 and lung cancer 26 . Moreover, numerous studies have identified BAR as an independent predictor for mortality risk of AMI 30,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood urea nitrogen (BUN) is the major product of protein metabolism in the human body and is primarily eliminated by the kidney. 9 BUN has been identified as a biomarker for renal function and was linked to the prognosis of various diseases, such as acute aortic dissection, 10 pancreatitis, 11 and acute intracerebral haemorrhage. 12 Recently, there has been growing attention towards the role of BUN in predicting cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BUN/albumin ratio (BAR) has been identified as a new predictor factor associated with the prognosis of many diseases, including pulmonary embolism, 18) sepsis, 19) STEMI, 20) and lung cancer. 21) Moreover, a retrospective cohort study including 1545 critically ill patients with chronic HF was conducted by Lin, et al They found BAR as an independent risk factor for in-hospital and 90-day mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…16) A study by Yano, et al revealed that high BUN levels were independently associated with an increased risk of all-cause death and HF readmission. 17) The mathematical ratio of BUN and ALB, namely blood urea nitrogen/albumin ratio (BAR), was identified as a new predictor factor and found to be associated with the prognosis of many diseases, including pulmonary embolism, 18) sepsis, 19) ST-elevation myocardial infarction (STEMI), 20) and lung cancer. This study aimed to evaluate the prognostic value of BAR for patients with HF.…”
mentioning
confidence: 99%